Fine root dynamics of oak saplings in response to Phytophthora cinnamomi infection under different temperatures and durations. Issue 2 (7th October 2014) - McConnell, M. E.; Balci, Y.; Woodward, S.
Summary The belowground effects of Phytophthora cinnamomi on 1‐year‐old saplings of two common oak species in mid‐Atlantic US forests, white (Quercus alba) and red oak (Q. rubra), were examined after incubation in pathogen‐infested soilless potting mix. Fine root lengths (0–1.5 mm in diameter) of both oak species were quantified after incubation at successive 30‐day intervals up to 300 days, for a total of 10 incubation periods. In addition, colony‐forming units (CFU) of P. cinnamomi were quantified after white oak saplings were incubated in infested soilless potting mix at different temperature/duration combinations that reflect soil conditions present in the mid‐Atlantic United States. Impact of P. cinnamomi on fine root lengths of red and white oak saplings varied considerably over time. Significant periods of fine root loss occurred primarily during spring, when bud break and leaf flush began for both oak species. Red oaks had 17% fine root loss on average, while white oaks appeared more resistant to P. cinnamomi infection with a 2% decrease in fine roots over the course of the experiment. Phytophthora cinnamomi CFU declined significantly with exposure to all incubation temperatures except 8°C. This was in contrast to in vitro experiments, where the optimum temperature for mycelial growth was determined to be 21°C and above. Significant fine root loss caused by P. cinnamomi depended on plant phenology and the oak species tested. Extreme soil temperatures have a significant adverse impact on temporal changes of P. cinnamomi population.